LITERARY PERCEPTION OF ONE’S OWN AND THE OTHER IN THE WORKS OF PETAR KOČIĆ - Valentina R. Milekić Kovačić (Filolog)
Key features of Kočić’s poetics are implied by the specific mentality portrayed by the author and by the manner of its representation, which is primarily reflected in a complex literary perception of one’s own and the Other. The image of the Other in Kočić’s oeuvre represents a literary reality, which, as such, remains insufficiently researched, and through which various poetic aspects of his works can be viewed. For that reason, considerations of the Other are at the core of this paper, within the theoretical-methodological framework ranging from imagology and mentality research. Imagological perspectives offer opportunities for new methodological topicalisation and revalorisations of Kočić’s oeuvre.